Pilot study: The association of perceived stress score and quality of sleep in type 2 diabetes mellitus patients at Hospital Pekan - Baharudin, Mohamad Sharul Fahmi; Jamshed, Shazia Qasim; Abdul Rahim, Roslina; Fauzee Andylim, Nizafaziasyida; Soe, May Khin Soe (2017)
Background: Stress is psychological unpleasant, but one of the most assessed life experiences among people worldwide. Stress is believed to affect eating behavior, blood glucose level, cholesterol level and obesity. Sleep is a fundamental biologic function and is essential for human functioning and well-being. Patients with Type 2 Diabetes Mellitus can experience challenges to their sleep and wakefulness due to physiological imbalance and co-morbid sleep pathologies. This pilot study compared the perceived stress score (PSS) and quality of sleep between Type 2 Diabetes Mellitus (T2DM) patients with healthy adults in Hospital Pekan, Pahang. Methods: The comparisons of the PSS and quality of sleep between two groups of subjects were explored for 10 respondents including 5 T2DM patients and 5 healthy adults. In this study, the consent form and the questionnaires were distributed to assess their PSS and quality of sleep as well as the validity of the tool. The result then being analyzed descriptively using SPSS version 21.0. Results: The mean value of both groups’ PSS score was found (31.80 ± 0.53). T2DM patients’ PSS was higher (34.20±7.01) with maximum PSS of 45.00 compared to healthy adults (29.40 ± 2.70.3), maximum PSS of 33.00. PSS validity analysis, the overall Cronbach alpha is 0.83. Meanwhile, the Pittsburgh Sleep Quality Index (PSQI) score was 7.40 ± 2.95 for both groups. T2DM’s PSQI is higher (7.60 ± 2.88) compared to healthy adults (7.20 ± 3.35). This indicates T2DM group experience poorer quality of sleep (global PSQI score > 7.40). Conclusion: Complications of diabetes mellitus such as polyuria, polyneuropathy and infections trigger the sleep deprivation and alertness at night. As a result, patients are complaining of sleep disturbance (high PSQI) and end being stressful. That chronic stressful condition deteriorates the normal physiological metabolism and causes the biochemical changes. All of these major complications cause high PSS in T2DM patients compared to healthy adults. Screening and management of stress and poor sleep quality is necessary to be involved in T2DM patients’ self- management to improve their quality of life.